You're looking for values of x and y that satisfy both equations at the same time. We can solve this by substitution, which involves solving one equation for one of the variables, then rewriting the other equation completely in terms of one of these variables, and solving for them.
In the second equation, we have
x - 4y = 3
which means
x = 4y + 3
Substitute this into the other equation and solve for the other variable:
4x - 4y = 24
4 (4y + 3) - 4y = 24
16y + 12 - 4y = 24
12y + 12 = 24
12y = 12
y = 1
Solve for the remaining variable:
x = 4y + 3
x = 4•1 + 3
x = 4 + 3
x = 7